Extent of Implementation of Nuc Regulation by Private Universities in Enugu State on Personnel Management - Chidobi, Roseline Unoma (American Journal of Education and Learning, 2017)
The purpose of this study is to investigate on the extent of implementation of NUC Regulations by Private Universities in Enugu State on Personnel Management. Descriptive survey design was employed in the study. The quantitative data were collected through a 24 item questionnaire title “Extent of Implementation of NUC Regulation on Personnel Management in private Universities (EINRPMPU)”. This was administered on 509 respondents made up of University principal Officers, head of units, lecturers and students. The data were analyzed using mean, standard deviation, t-test and z-score on a modified 4 point rating scale. Findings of the study revealed among others. Private universities in Enugu State adhere to NUC regulations regards to staff personnel and student personnel management. Based on the above some recommendations were made.